2004
DOI: 10.5194/nhess-4-563-2004
|View full text |Cite
|
Sign up to set email alerts
|

Pressure stimulated currents in rocks and their correlation with mechanical properties

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects" Abstract. The spontaneous electrification of marble samples was studied while they were subjected to uniaxial stress. The Pressure Stimulated Current (PSC) technique was applied to measure the charge released from compressed Dionysos marble samples, while they were subjected to cyclic loading. The experimental results demonstrate that, in the linear elastic region of the sample, no PSC is recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 17 publications
2
51
0
1
Order By: Relevance
“…An intense PSC signal with repeated spikes is also detected under high constant uniaxial stress, associated with variations in strain rate [31,32]. This paper outlines experimental techniques to measure Pressure Stimulated Currents (PSC) on CBM, and compares the results with those obtained from rock materials [11,[16][17][18][19][20]. The PSC measurements are systematically recorded while the samples are subjected to temporally varying axial compressive stress, either with a short duration and high repetition rate, or at a low-rate stress increase up to fracture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An intense PSC signal with repeated spikes is also detected under high constant uniaxial stress, associated with variations in strain rate [31,32]. This paper outlines experimental techniques to measure Pressure Stimulated Currents (PSC) on CBM, and compares the results with those obtained from rock materials [11,[16][17][18][19][20]. The PSC measurements are systematically recorded while the samples are subjected to temporally varying axial compressive stress, either with a short duration and high repetition rate, or at a low-rate stress increase up to fracture.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] From the very first experimental results it became evident that the characteristics of the electric signals indicate that the procedure of crack formation and development is accompanied by the creation of electric polarization [15,11]. On the other hand, the dominant relationship between stress variation rate, the electric charge released and the damage parameter when a sample is subjected to uniaxial compressive stress up to failure, was investigated [16,17]. After systematic measurements, a description of the pressure stimulated electric signals was attempted successfully using statistical mechanics methodology [23] while a linear correlation between the electric charge and the strain before the failure limit was ascertained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation mechanism/s is/are still uncertain but include the electrokinetic effect of moving water [6,7], piezoelectric effect of quartz [6,8], rock fracture (contact and separation of fresh surfaces) [9], and moving charge dislocations [10,11]. Some of these studies have shown that pressure stimulated current (PSC) emissions are related to a change in Young's modulus [12] and variations in PSC are observed beyond the linear elastic limit in marble specimens [13]. PSCs are also associated with high amplitude acoustic emissions (AE) events and high event rates in cement mortar beams [14].…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanoelectrical transformations can occur during initiation processes. Laboratory experiments show that rocks, even those that do not contain piezoelectric minerals, can generate EM emissions in a wide frequency range under mechanical stress, as well as pressurestimulated currents (Anastasiadis et al, 2007;Rabinovitch et al, 1998;Stavrakas et al, 2004;Freund, 2007;Triantis et al, 2007;Yasuhiko et al, 2009). We need to mention that, usually, published papers represent the results of experiments carried out with only one type of mechanical influence like loading, with the subsequent fracture of the samples or gradual loading without failure; impact; rubbing samples with, as a rule, smoothed surfaces.…”
Section: Introductionmentioning
confidence: 99%